A Case Report of an Unusual Case of Tuberculous Osteomyelitis Causing Spontaneous Pathological Fracture of Humerus in a Middle Aged Female - Birole, Umesh (J Orthop Case Rep, 2017)
INTRODUCTION: Tuberculosis is a major health problem worldwide. Extrapulmonary tuberculosis is often secondary to some primary foci in lungs. There are reports of tuberculous osteomyelitis involving maxilla, ulna, femur, and shoulder joint but none have reported pathological fracture in humeral diaphysis due to tuberculosis osteomyelitis without shoulder joint involvement. We report a case of pathological fracture of humerus diaphysis due to tuberculous osteomyelitis with normal articular space. We noticed favorable outcome following surgery and antitubercular drugs. CASE REPORT: A 62-year-old female diabetic patient presented with complaints of pain in the right shoulder of 2 weeks duration and inability to raise right arm. Initial clinical evaluation revealed local rise of temperature, tenderness over the right shoulder and proximal arm and restricted range of movements in all plane. Neurologically, the patient was normal. Erythrocyte sedimentation rate was raised. Computed tomography chest showed small area of consolidation in the left upper lobe. Plain radiograph of the right shoulder with humerus showed transverse fracture of proximal shaft of the right humerus. J-needle biopsy was done from proximal humerus fracture site. Histopathological examination of biopsy tissue from fracture site confirmed granuloma with epithelioid and Langhan’s giant cells. Mantoux test and culture for acid-fast bacilli were non-conclusive. Based on histopathology report, we concluded this to be tuberculous osteomyelitis of humerus and the patient was started on category 1 antitubercular drugs, under Revised National Tuberculosis Control Programme as per revised WHO guidelines. We performed open debridement and fixation of fracture with rush nail. Initial follow-up 4 months, post-operative and plain radiograph showed overall improvement in general condition of the patient, weight gain, and good fracture healing. One year following index surgery, rush nails were removed due to pain at insertion site. Fracture healed completely. Shoulder abduction and forward flexion were restricted in terminal 30°, internal and external rotation, and adduction was full compared to opposite shoulder. CONCLUSION: Tuberculosis is very common in India, but its presentation as spontaneous fracture of humerus is unusual. It is highly likely that most orthopedician will encounter and treat tuberculosis and our case highlights the high degree of suspicion one must have in diagnosing pathological fracture of long bones. Error in diagnosis and treatment burdens the medical resources and overall morbidity.